KARAKTERISTIK ORGANOLEPTIK DAN FISIKOKIMIA KOPI JAHE CELUP PADA VARIASI TINGKAT PENYANGRAIAN DAN KONSENTRASI BUBUK JAHE - Mukhammad Fauzi; Noer Novijanto; Dhuita Puspita Rarasati (JURNAL AGROTEKNOLOGI, 2019)
Coffee is one of the plantation commodities that have high economic value. Coffee beans generally process become roasted coffee beans or ground coffee. Brewed ground coffee still leave the dregs when it mix with boiling water. The effort to reduce the dregs of the ground coffee is making dip coffee products. One of the new innovations was make healthful coffee products with ginger, namely coffee-ginger bag. Ginger rhizome contains bioactive compounds such as phenolic compounds (shogaol and gingerol) and essential oils, such as bisapolen, zingiberen, zingiberol and curcumen, that act as antioxidants. Different roasting level of coffee and concentration of ginger powder affected the flavor and aroma of coffee-ginger bag. The results showed that the most preferred coffee-ginger bag was dip ginger coffee roasted on dark level and 6% ginger powder concentration. It had total polyphenol of 98.72 μg GAE/ml with the antioxidant activity of 44.31%. Coffee-ginger bag roasted on dark level and 6% ginger powder concentration had lightness of 39.4. The highest total content of dissolved solids was coffee-ginger bag roasted on dark level and 0% ginger powder concentration which reached 13.12 mg/ml. Keywords: antioxidants, coffee, ginger, polyphenols, roasting